Leadership Style and Employee Performance: The Case of Oil and Gas Industry - Thomas, Basil John (American Journal of Social Sciences and Humanities, 2020)
Here an attempt is made to investigate the leadership style eventually practiced in the organisations and its impact on the perpetual development of the employee performance particularly considering the Oil and Gas Industry of Oman. The study eventually has found that it is the responsibility of the leaders who can motivate the workforce to move in a right direction to achieve the destined goals. The study has also found that in the current scenario where the Western world is trying to establish their entity in the oil and gas business, if an organisation is not guided properly by a leader, chances of crumbling down before the intense pressure is quite common. The study has also essentially found that autocratic leadership style is quite effective in the short term while the democratic leadership style is useful for all time. The study recommends that a leader should be proactive in nature and must be capable of understand the internal and external scenario that the organisation is currently facing or would have to face in the coming days. It would help the leader guide the workforce through the proper channel and attain the predestined objectives set beforehand.